3D full-space triboelectric-electromagnetic hybrid nanogenerator for high-efficient mechanical energy harvesting in vibration system. (1st March 2020) - He, Jian; Fan, Xueming; Mu, Jiliang; Wang, Chao; Qian, Jichao; Li, Xiucheng; Hou, Xiaojuan; Geng, Wenping; Wang, Xiangdong; Chou, Xiujian
Abstract: Mechanical energy with low frequency is a widely distributed energy in environment. Triboelectric nanogenerator (TENG) and electromagnetic energy harvester (EMG) are considered as promising methods to harvest low-frequency mechanical energy. In this study, a three-dimensional (3D) full-space triboelectric-electromagnetic hybrid nanogenerator (FSHG) based on a magnetic ball and Polystyrene (PS) spherical shells is presented. The external excitation can be transformed into the relative motion between different units. The mover composed of the PS spherical shell 3 and a magnet ball transforms 3D full-space mechanical energy into electrical energy through friction electrification and electromagnetic induction effect. The results of experiments show that the performance of TENG and EMGs can be influenced by the direction of external vibration and excitation frequency. The output performances of TENG and EMGs increase as the excitation frequency increases. The results show that the maximum output power of TENG is 18 μW at an external loading resistance of 200 MΩ, and the maximum output power of EMG is 640 μW at an external loading resistance of 1000 Ω. The FSHG demonstrates a quick charging ability for capacitor and the capability to power hundreds of LEDs. After storing energy in the capacitor, the DC signal can power a humidity/temperature sensor. Highlights: The device can harvest energy from all directions rather than a single direction. A harvester combined with TENG and EMG can harvest energy at wider frequencies. Energy capture can be improved by the moveable magnet ball and PS shell.